Razvoj generične strukture in programskih modulov elementarnega delovnega sistema porazdeljenega tiskanja - Rotar, Franc (Strojniški vestnik, 2006)
The traditional manufacturing system paradigm has deficiencies in the modern, global world related to market demands, which are changing so quickly that only the most agile manufacturers can follow them. In response, new manufacturing paradigms have evolved in recent decades. Of these, the holonic,bionic, fractal factory and complex adaptive manufacturing systems (CAMS) paradigms are the most popular. CAMS principles are being used and CAMS objects (virtual work systems) are built in order to deliver a distributed solution for product labeling at various levels in a company that has production plants around Europe. Modern information and communication technologies (ICTs) are being utilized to build a system that produces labels at n locations based on the demands from m places. It is the company's policy,not the concept or the implementation issues, that limits the size and the functionality of the presented labeling system in a distributed environment.
Keywords: sistemi proizvodni; kooperacija; sistemi delovni; strukture dejavne; organizacija podjetja; proizvodni sistemi